2014
DOI: 10.1002/2014gl061222
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microphysics on the scaling of precipitation extremes with temperature

Abstract: Simulations of radiative-convective equilibrium with a cloud-system resolving model are used to investigate the scaling of high percentiles of the precipitation distribution (precipitation extremes) over a wide range of surface temperatures. At surface temperatures above roughly 295 K, precipitation extremes increase with warming in proportion to the increase in surface moisture, following what is termed Clausius-Clapeyron (CC) scaling. At lower temperatures, the rate of increase of precipitation extremes depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 27 publications
5
100
0
Order By: Relevance
“…Sen Roy and Balling, 2004;Rajeevan et al 2008;Pattanaik and Rajeevan 2010;Westra et al 2014) and model studies (e.g. Frei et al 1998;Muller et al 2011;Singh and O'Gorman 2014). Our results clearly show a shift in the precipitation categories, with more extreme precipitation in the perturbed runs.…”
Section: Discussionsupporting
confidence: 53%
“…Sen Roy and Balling, 2004;Rajeevan et al 2008;Pattanaik and Rajeevan 2010;Westra et al 2014) and model studies (e.g. Frei et al 1998;Muller et al 2011;Singh and O'Gorman 2014). Our results clearly show a shift in the precipitation categories, with more extreme precipitation in the perturbed runs.…”
Section: Discussionsupporting
confidence: 53%
“…The differences may have various origins which are not accounted for by our simple scaling, such as model uncertainty (e.g. convection and microphysics parameterizations; Singh and O'Gorman 2012), change in precipitation duration (and thus impact on averaging effect), change in precipitation efficiency or vertical moisture transport in a more arid environment (Paltridge et al 2009;Zhang 2009;Drobinski et al 2016). The ratio of 3-hourly to daily precipitation extremes in the low-resolution simulations increases with warming (not shown), suggesting shorter extreme precipitation events and thus a steeper negative slope at high temperature for daily precipitation accumulation.…”
Section: (S)mentioning
confidence: 99%
“…Indeed, Parodi and Emanuel (2009) found that the fall speed of hydrometeors plays an important role in determining convective updraft velocities in RCE; a low fall speed results in clouds with higher condensed water contents and thus reduced buoyancy via the water loading effect. Hydrometeor fall speeds, and microphysical processes more generally, are sensitive to temperature changes (Singh and O'Gorman 2014) and thus may contribute to changes in updraft velocity as the atmosphere warms.…”
Section: Introductionmentioning
confidence: 99%